Ethical problems in public accounting: The view from the top - Finn, Don W. (Journal of business ethics, 1988)
The authors empirically examine the nature and extent of ethical problems confronting senior level AICPA members (CPAs) and examine the effectiveness of partner actions and codes of ethics in reducing ethical problems. The results indicate that the most difficult ethical problems (frequency reported) were: client requests to alter tax returns and commit tax fraud, conflict of interest and independence, client requests to alter financial statements, personal-professional problems, and fee problems. Analysis of attitudes toward ethics in the accounting profession indicated that (1) CPAs perceive that opportunities exist in the accounting profession to engage in unethical behavior, (2) CPAs, in general, do not believe that unethical behavior leads to success, and (3) when top management (partners) reprimand unethical behavior, the ethical problems perceived by CPAs seem to be reduced.